Specific heat study of magnetic excitations in a one-dimensional S =1 Heisenberg magnet with strong planar anisotropy - Feher, A.; Orendáč, M.; Orendáčová, A.; Čižmár, E. (Физика низких температур, 2002)
The results of experimental studies of the specific heat of the magnetic chain compounds Ni(C₂H₈N₂)₂Ni(CN)₄, Ni(C₁₁H₁₀N₂O)₂Ni(CN)₄, and Ni(C₁₀H₈N₂)₂Ni(CN)₄⋅H₂O are reported. All compounds are identified as S=1 planar Heisenberg magnetic chains with large planar anisotropy and different values of the in-plane anisotropy constant. The low-temperature specific heat data are interpreted assuming the existence of noninteracting excitons and antiexcitons as elementary excitations from the singlet-ground state. The extended strong-coupling model is used for analysis of the data at higher temperatures. The applicability of the models used with respect to the value of the in-plane anisotropy is discussed.